Priopoda macrophyae (Hymenoptera, Ichneumonidae, Ctenopelmatinae), a new species of parasitoid of Macrophya satoi (Tenthredinidae), a serious pest of Japanese ash tree (Oleaceae) - Watanabe, Kyohei (Zootaxa, 2023)
A new species, Priopoda macrophyae sp. nov., is described. This species is an important parasitoid of a serious pest of Japanese ash (Fraxinus japonica), Macrophya satoi Shinohara & Li, 2015. This species resembles P. otaruensis (Uchida, 1930) in the black colouration of the hind coxa, hind femur, and all metasomal tergites, but can be clearly distinguished by the length of the malar space, the smooth interspace of the punctures on the mesopleuron, the large smooth area of the speculum, the complete and strongly raised propodeal carinae, and the length of the first metasomal tergite. The bionomics of this species is also noted. The host record of this species is also the first record for Asian species of this genus.